2020
DOI: 10.1093/femsec/fiaa027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microbiota, antimicrobial resistance genes and mobile genetic elements in flies and the feces of sympatric animals

Abstract: Flies are well-known vectors of bacterial pathogens, but there are little data on their role in spreading microbial community and antimicrobial resistance. In this study, we compared the bacterial community, antimicrobial resistance genes (ARGs) and mobile genetic elements (MGEs) in flies with those in the feces of sympatric animals. A 16S rRNA-based microbial analysis identified 23 bacterial phyla in fecal samples and 25 phyla in flies; all the phyla identified in the fecal samples were also found in the flie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…This aspect is very important, since it is known that the insect presence can have an influence on the microbial composition of the feeding substrate. Concerning the blowfly’s ability to perform the microbiome exchange in and from the living environment, carrying and transmitting pathogens, was demonstrated by the same microbial patterns identified both in flies and the feces of sympatric animals 9 . Additionally, during the decomposed tissue pre-digestion, blowflies secrete certain enzymes that have antimicrobial actions, thus having the potential to alter the microbial pattern of the substrate 36 , 57 .…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This aspect is very important, since it is known that the insect presence can have an influence on the microbial composition of the feeding substrate. Concerning the blowfly’s ability to perform the microbiome exchange in and from the living environment, carrying and transmitting pathogens, was demonstrated by the same microbial patterns identified both in flies and the feces of sympatric animals 9 . Additionally, during the decomposed tissue pre-digestion, blowflies secrete certain enzymes that have antimicrobial actions, thus having the potential to alter the microbial pattern of the substrate 36 , 57 .…”
Section: Discussionmentioning
confidence: 86%
“…Regarding the overall microbiome characterization, studies investigating the fly’s bacterial content showed that Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria prevailed in both blowfly and housefly life stages 9 , 13 , 46 , while another study 36 revealed that Flavobacteria dominated the pupa stage. Singh and collaborators research 36 showed that the microbiome pattern was specific and similar for the adult and larva stages, being characterized by Firmicutes with Lactobacillales, for the pupa being dominated by Proteobacteria with the greatest order and family diversity, and for the teneral stage prevailing Actinobacteria with Corynebacteriales.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations